Adhesion and Cell Viability of Normal Human Osteoblasts (NHOst) on Scaffolds of Poly (3-hydroxybutyrate). Issue 1721 (13th February 2015) - Domínguez-Díaz, Maraolina; Meneses-Acosta, Angelica; Romo-Uribe, Angel
ABSTRACT: Biodegradable Normal Human Osteoblast (NHOst) cells were inoculated into the polymer scaffolds of poly(β-hydroxybutyrate) (PHB) obtained from a specially developed strain of Azotobacter vinelandii . Cell adhesion is essential to promote growth on scaffolds for tissue engineering. Thus, in this research we focused on the adhesion of osteoblast cells to PHB scaffolds produced by solution casting and electrospinning. Cell viability was also investigated up to 168 hrs. Water contact angle on the PHB scaffolds was determined prior to the cells inoculation. The contact angle is usually related to the ability of different cell strains to adhere to a given material. The as cast film exhibited a contact angle α=72° whereas for the electrospun membrane α=102°, thus in theory cell adhesion would be greater for the cast film. Biological testing was carried out on plates of 24 wells; cell viability was determined by Trypan Blue, cell morphology by optical microscopy, and cell nuclei integrity by staining with Acridine orange. Parallel studies were carried out on control (empty) wells. Microscopy observations 168 hrs after cell inoculation showed larger quantities of osteoblast cells in the wells containing PHB scaffolds and the cell nuclei were still active. Moreover, it was found that the cells grew inside the PHB scaffolds and the cell viability was slightly greater for the electrospun scaffold. Interestingly, the time to remove the cells from the scaffolds (film and membranes) was increasing function of the cell culture time, therefore suggesting that PHB promotes adhesion of Normal Human Osteoblast cells to its surface.